核桃仁颜色与化学成分的关联分析 "Correlation analysis between color and chemical composition of walnut kernels" - 孙诗曼，郑悦雯，李庆杨，莫润宏，汤富彬，刘毅华 SUN Shiman，ZHENG Yuewen，LI Qingyang，MO Runhong，TANG Fubin，LIU Yihua (Zhongguo youzhi)
旨在为核桃高品质育种和深化功能性产品开发提供参考，对新疆地区13份核桃仁的灰度值进行测定，以灰度值为指标进行聚类分析，将13份核桃仁分为浅色核桃仁和深色核桃仁2组，对2组核桃仁的含油率、主要化学成分（气味物质、脂肪酸、生育酚、总酚、矿质元素）进行测定，并采用正交偏最小二乘判别分析（OPLS-DA）和皮尔逊法对核桃仁颜色与化学成分进行关联分析。结果表明：聚类分析得到浅色核桃仁和深色核桃仁的灰度值分别为93.13~99.88和60.72~68.66；2组核桃仁的含油率和气味物质无显著差异（p>0.05）；浅色核桃仁的花生烯酸、γ-生育酚、总生育酚、总酚、P、Ca、Mn、Fe、Na、Ba含量显著高于深色核桃仁（p<0.05），深色核桃仁在棕榈酸、亚油酸、δ-生育酚、Zn含量中具有优势；OPLS-DA结果表明，Ba、Ca、Mn含量的变量权重值（VIP）最高，分别为2.39、2.21和2.07;皮尔逊法分析表明亚麻酸、花生酸、硬脂酸、饱和脂肪酸和Co含量与核桃仁灰度值呈显著负相关，棕榈油酸、K、Cu含量与核桃仁灰度值呈显著正相关。综上，核桃仁颜色与化学成分存在一定关联，可用于对核桃品质的预测。 To provide reference for high quality breeding and deepen the development of functional products，the gray values of 13 walnut kernels from the Xinjiang region were measured, and cluster analysis was conducted using gray value as an indicator, resulting in the 13 walnut kernels being divided into two groups: light-colored walnut kernels and amber walnut kernels. The oil content and major chemical components (aroma compounds, fatty acids, tocopherols, total phenol and mineral elements) of the two groups of walnut kernel were measured. Using orthogonal partial least squares discriminant analysis (OPLS-DA) and Pearson′s method to conduct correlation analysis between walnut kernel color and chemical composition.The results showed that light-colored walnut kernels with gray values ranging from 93.13 to 99.88, and amber walnut kernels with gray values ranging from 60.72 to 68.66. There were no significant differences in oil content and aroma compounds between the two groups (p>0.05). The light group demonstrated significantly higher levels of eicosenoic acid, γ-tocopherol, total tocopherols, total phenol, P, Ca, Mn, Fe, Na and Ba compared to the amber group (p<0.05). In contrast, the amber group exhibited elevated concentrations of palmitic acid, linoleic acid, δ-tocopherol and Zn content. OPLS-DA results indicated that the contents of Ba, Ca and Mn had the highest variable importance in projection values (VIP) at 2.39, 2.21 and 2.07, respectively. Pearson′s method analysis indicated that the contents of linolenic acid, arachidic acid, stearic acid, saturated fatty acids, and Co content were significantly negatively correlated with the gray value of walnut kernels, while the contents of palmitoleic acid, K and Cu were significantly positively correlated with the gray value of walnut kernels.In summary, there is a certain correlation between the color of walnut kernels and their chemical composition, which can be used for predicting the quality of walnuts.